What Patients and Partners Want in Interventions That Support Sexual Recovery After Prostate Cancer Treatment: An Exploratory Convergent Mixed Methods Study. Issue 2 (1st March 2019) - Mehta, Akanksha; Pollack, Craig Evan; Gillespie, Theresa W.; Duby, Ashley; Carter, Caroline; Thelen-Perry, Steve; Witmann, Daniela
Abstract: Introduction: Men treated for prostate cancer suffer from treatment-related sexual side effects that adversely affect their relationships and quality of life. Aim: To investigate what prostate cancer survivors and their partners want from a sexual recovery intervention, and whether they consider an online tool acceptable for use in promoting sexual recovery. Methods: This mixed-methods study included focus groups and interviews with both heterosexual and gay cancer survivors, as well as their partners. Focus groups and interviews probed experiences with treatment, side effects, and support received/needed for sexual recovery. Participants responded to proposed web-based intervention content. Interviews were analyzed with thematic content analysis. Their sexual function was assessed with validated measures. Main Outcome Measures: Acceptability of online tools for promoting sexual recovery was evaluated. Results: Participants included 14 patients and 10 partners (2 male). Patient and partner median age was 62 and 62.5 years, respectively. Treatment ranged from surgery alone to combined radiation and hormonal therapy. Qualitative data analysis yielded 5 main intervention needs: (i) pretreatment discussion of sexual side effects, rehabilitation, emotional impact and realistic expectations, (ii) improved sexual communication within couples, (iii) strategies for promoting sexual intimacy beyond penetrative intercourse, (iv) attentiveness to partners' needs, and (v) access to peer support. Gay men specifically expressed the need for improved provider understanding of their sexuality and experiences. Most considered a web-based approach to be acceptable. Conclusion: Patients and partners value both pretreatment preparation for sexual recovery and support for sexual recovery for both after treatment. A web-based approach may help mitigate barriers to access to these support services.